Optimizing Classroom and Activity-Based Character Education: A Comprehensive Guide to Best Practices and Implementation Strategies in Early Childhood Education - Handoko, Sigit; Sakti, Syahria Anggita (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga, Yogyakarta, 2023)
This research aims to provide an exhaustive investigation into the best practices and implementation strategies inherent to classroom and activity-based Character Education Programs within the context of early childhood education. The study meticulously outlines critical variables such as careful program planning, diverse learning strategies, active student participation, and the pivotal role of teacher support. Results reveal five essential best practices and implementation techniques: meticulous planning, utilization of varied learning approaches, encouragement of active student involvement, ongoing program evaluation, and alignment with extant literature. Furthermore, the study emphasizes the integral function of teachers as both instructors and environmental architects. Implications extend to educational practitioners and policymakers by offering a robust program design, implementation, and assessment framework. Despite the comprehensive scope, limitations include the specificity to early childhood contexts, calling for broader research into varied educational levels. The study thereby contributes a nuanced perspective to existing literature and is an indispensable resource for stakeholders in education.